Strategi Coping Stres Waria Pekerja Seks Komersial di Denpasar Bali - Putu Pricilia Santih; I Rai Hardika; I Wayan Damayana (Universitas Kristen Maranatha, 2022)
The phenomenon of transvestites raises public debates about those who are supporting, against and even abstentions about it. The lack of opportunities to express themselves in society makes transvestites alienated thus most of them choose to work as prostitutes. Transvestite's decision in determining gender identity and her work was rejected by family and society. The pressure and discrimination provided is considered as unpleasant events causing transvestites to feel stressed. The goal of this study is to explore the dynamics and coping strategies of the source's stress when addressing unpleasant circumstances. The method used is a case study with a qualitative approach. Data collection through interviews, observations and documentation is carried out to sources who are transvestites of PSK in Denpasar. The results showed that source L tend to use problem focused coping whilst source C tend to use emotional focused coping.